U podstaw myśli etycznej Leszka Kołakowskiego - Olczyk, Adam (Filozofia Publiczna i Edukacja Demokratyczna, 2016)
The article discusses primary matters of Leszek Kołakowski’s ethical thought. For that purpose, the analysis focuses on the need to justify the content of natural law. Kołakowski maintains that the development of communication and growth of cities are foundations of the justification process. In line with this idea the intuition of evil (related with such terms like tabu, sacrum, profanum or sin) is the major determinant for the distinction between good and evil. Kołakowski’s theory also explores a connection between the experience of evil and human dignity.